2016
DOI: 10.5194/tc-10-1845-2016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced melt on debris-covered glaciers: investigations from Changri Nup Glacier, Nepal

Abstract: Abstract. Approximately 25 % of the glacierized area in the Everest region is covered by debris, yet the surface mass balance of debris-covered portions of these glaciers has not been measured directly. In this study, ground-based measurements of surface elevation and ice depth are combined with terrestrial photogrammetry, unmanned aerial vehicle (UAV) and satellite elevation models to derive the surface mass balance of the debris-covered tongue of Changri Nup Glacier, located in the Everest region. Over the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
156
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 139 publications
(171 citation statements)
references
References 54 publications
12
156
1
2
Order By: Relevance
“…Given that these features typically contribute ∼ 10-20 % of the total melt (Sakai et al, 2000;Reid and Brock, 2014), it is unlikely that they can lower the glacierwide mean melt rate on debris-covered glaciers sufficiently so that it matches that on the debris-free glaciers. Field measurements by Vincent et al (2016) seem to confirm this. It was also conjectured that a reduction in ice flux from upstream areas to the stagnant tongue may be behind the largerthan-expected thinning of debris-covered glacial ice (Kääb et al, 2012;Gardelle et al, 2012).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Given that these features typically contribute ∼ 10-20 % of the total melt (Sakai et al, 2000;Reid and Brock, 2014), it is unlikely that they can lower the glacierwide mean melt rate on debris-covered glaciers sufficiently so that it matches that on the debris-free glaciers. Field measurements by Vincent et al (2016) seem to confirm this. It was also conjectured that a reduction in ice flux from upstream areas to the stagnant tongue may be behind the largerthan-expected thinning of debris-covered glacial ice (Kääb et al, 2012;Gardelle et al, 2012).…”
supporting
confidence: 69%
“…Also, it was reported that in the Pamir-Karakoram-Himalayas, depending on the region chosen, geodetic measurement yielded decadal thinning rates of debris-covered ice that were either larger or smaller than, or similar to that of debris-free ice (Gardelle et al, 2013). The present scenario is summed up neatly by Vincent et al (2016), "This question of areaaveraged melting rates over debris-covered or clean glacier ablation areas remains unanswered".…”
mentioning
confidence: 99%
“…The energy balance drives the melt of the debris-covered tongues and several studies point toward a yet unexplained faster surface lowering of the tongues of these glaciers than what can be expected based on the melt suppression by thick debris (Kääb et al, 2012;Gardelle et al, 2013;Pellicciotti et al, 2015;Azam et al, 2018). It is unclear whether this behavior can be attributed to turbulent fluxes, supra-glacial features such as cliffs and ponds, a reduced emergence velocity or other processes (Vincent et al, 2016;Azam et al, 2018). Highly detailed information about the surface temperature provides LW ↑ , a term often assumed to be spatially constant and only measured point-scale at a weather station (Reid et al, 2012;Steiner and Pellicciotti, 2016).…”
Section: Applications Of Thermal Uav Imagerymentioning
confidence: 86%
“…The emergence velocity (w e ) of ice for debris-covered glaciers has been found to be significantly different from zero for 25 some cases, but it has typically been neglected in the calculation of p. Values of w e equal to 5.7-6.4 ± 3.9 m a −1 (Nuimura et al, 2011), 0.41 ± 0.05 m a −1 (Vincent et al, 2016) and 0.00-0.35 ± 0.10 m a −1 (Nuimura et al, 2017) have been found for, respectively, the debris-covered tongues of Khumbu, Changri Nup and Lirung glaciers in Nepal. Emergence velocities will affect the thinning rates of debris-covered ice and ice cliffs equally.…”
mentioning
confidence: 99%